2019
DOI: 10.1002/cctc.201900146
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Polydopamine Modified Carbon Nanotube Hybrids and their Catalytic Activity in Ethylbenzene Dehydrogenation

Abstract: A new synthetic strategy was developed for the fabrication of polydopamine modified carbon nanotube catalysts via in situ polymerization and subsequent thermal treatment process. The hybrid nonmetallic catalysts exhibited superior apparent and intrinsic activity than undoped or nitrogen doped carbon nanotube materials in ethylbenzene dehydrogenation reactions. The relatively high catalytic activity could be attributed to the electron transfer from polydopamine to nanocarbon matrix. The immediate result is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…More detailed results were obtained by deconvolution of the XPS O 1s and N 1s spectra, which provided evidence for several different O and N species being distributed on the carbon-rich surfaces (Figure ). In the N 1s core region, four main components at 398.9 eV (±0.1 eV), 400.2 eV (±0.1 eV), 401.6 eV (±0.2 eV), and 405.8 eV (the latter one exceptionally for SK) were distinguished and attributed to pyridinic, pyrrolic, quaternary nitrogen, and oxidized nitrogen species, respectively. , In turn, in the O 1s spectra, three essential peaks appeared at 531.1 eV (±0.1 eV), 532.2 eV (±0.1 eV), and 533.8 eV (±0.1 eV) and were assigned to CO (oxygen atom in carbonyl), OC–O (oxygen atom in ester, anhydride and carboxylic acid), and C–O (oxygen atom in phenol/ether), respectively. , Furthermore, one more component was found at 533.3 eV for the HNO 3 treated sample (SK) and assigned to nitro groups . Obviously, during the modification of SK with NH 3 (sample SK_N), the nitro species were reduced completely, forming mainly pyridinic and pyrrolic functionalities (cf.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…More detailed results were obtained by deconvolution of the XPS O 1s and N 1s spectra, which provided evidence for several different O and N species being distributed on the carbon-rich surfaces (Figure ). In the N 1s core region, four main components at 398.9 eV (±0.1 eV), 400.2 eV (±0.1 eV), 401.6 eV (±0.2 eV), and 405.8 eV (the latter one exceptionally for SK) were distinguished and attributed to pyridinic, pyrrolic, quaternary nitrogen, and oxidized nitrogen species, respectively. , In turn, in the O 1s spectra, three essential peaks appeared at 531.1 eV (±0.1 eV), 532.2 eV (±0.1 eV), and 533.8 eV (±0.1 eV) and were assigned to CO (oxygen atom in carbonyl), OC–O (oxygen atom in ester, anhydride and carboxylic acid), and C–O (oxygen atom in phenol/ether), respectively. , Furthermore, one more component was found at 533.3 eV for the HNO 3 treated sample (SK) and assigned to nitro groups . Obviously, during the modification of SK with NH 3 (sample SK_N), the nitro species were reduced completely, forming mainly pyridinic and pyrrolic functionalities (cf.…”
Section: Resultsmentioning
confidence: 96%
“…60,61 In turn, in the O 1s spectra, three essential peaks appeared at 531.1 eV (±0.1 eV), 532.2 eV (±0.1 eV), and 533.8 eV (±0.1 eV) and were assigned to CO (oxygen atom in carbonyl), OC−O (oxygen atom in ester, anhydride and carboxylic acid), and C−O (oxygen atom in phenol/ether), respectively. 62,63 Furthermore, one more component was found at 533.3 eV for the HNO 3 treated sample (SK) and assigned to nitro groups. 64 Obviously, during the modification of SK with NH 3 (sample SK_N), the nitro species were reduced completely, forming mainly pyridinic and pyrrolic functionalities (cf.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, in the XPS N 1s spectra, three peaks at 398.6 ± 0.3, 400.2 ± 0.2, and 401.5 ± 0.2 eV were distinguished as a result of deconvolution. They could be attributed to the presence of pyridinic N, pyrrolic N, and graphitic N, respectively [ 45 , 46 , 47 ]. Interestingly, in the case of the samples exposed to the nitric acid solution (“ox” series), additional components exceptionally appeared in the XPS spectra, i.e., at 533.2 ± 0.2 eV for O 1s and 404.4 ± 0.3 eV for N 1s.…”
Section: Resultsmentioning
confidence: 99%
“…[ 15‐19 ] In the case of the oxidative dehydrogenation of ethylbenzene, both experimental and theoretical results have confirmed that the activation of the aliphatic C—H bond on the ethyl group is the rate‐determining step in this reaction, [ 20 ] and the nucleophilicity of catalyst can increase ethylbenzene catalytic activity. [ 21‐22 ] Because B in BPO 4 always remains in the +3 oxidation state, the electron density of BO 4 is relatively larger than that of BO 3 . The presence of the excess electron density in BO 4 is expected to perturb the binding strength of 1s electron and shift the bind energy to a lower value, which led to more nucleophilic of the oxygen in BO 4 .…”
Section: Background and Originality Contentmentioning
confidence: 99%